Penguasaan lahan dan pola tanam: implikasinya pada produktivitas lahan pertanian: Land tenure and cropping patterns: implications for agricultural land productivity - Yofa, Rangga Ditya; Susilowati, Sri Hery; Sumedi (Analisis Kebijakan Pertanian, 2025)
Farmers' strategies for maximizing household income from agricultural businesses involve optimizing cropping patterns. Agricultural land productivity is the level of income per hectare obtained by farmers in one year from implementing a cropping pattern. This study aims to formulate policy recommendations for increasing farmer income through cropping pattern arrangements. The data used are from the National Farmers Panel (Patanas) from the Indonesian Center for Agricultural Socio-Economics and Policy Studies (ICASEPS), Ministry of Agriculture, for the 2016-2023 period. The data were analyzed using quantitative descriptive methods. The results show that (1) fewer farmers own land and more farmers rent land; (2) the highest land productivity occurs in dry land vegetable agroecosystems by implementing a potato−potato−potato cropping pattern, but only a few farmers can apply this; (3) in irrigated rice field agroecosystems, an increase in the rice planting index does not guarantee a significant increase in land productivity; and (4) the dynamics of land productivity in irrigated rice field agroecosystems show that consistently in the three analysis periods, the majority of farmers implemented the rice−rice−fallow (IP200) cropping pattern which produced relatively high productivity and was not significantly different from the rice−rice−rice cropping pattern (IP300). The recommended policy includes developing farmer economic institutions, utilizing agricultural machinery to increase labor cost efficiency, implementing a selective increase in the rice planting index, and promoting the need for commodity rotation in dry land vegetable agroecosystems.